Exaggerated interpretation bias for uncertain information as a predictor of anxiety-related symptoms: A new method of assessment for IU. (September 2019) - Oglesby, Mary E.; Stentz, Lauren A.; Portero, Amberly K.; King, Savannah L.; Schmidt, Norman B.
Abstract: Background and objectives: Intolerance of uncertainty (IU), or fear of the unknown, is as an important transdiagnostic risk factor across anxiety-related conditions, namely generalized anxiety disorder (GAD), obsessive compulsive disorder (OCD), and social anxiety disorder (SAD). IU is typically indexed using self-report measures. Given the importance of multi-method assessments and the shortcomings associated with existing behavioral indices of IU, additional methods of assessment are needed. Emerging literature supports the use of interpretation bias (IB) paradigms to index constructs such as IU. However, only one study to date has examined the association between an IU-focused IB paradigm (IU-IB) and self-report IU and no research has investigated whether an IU-IB paradigm would be related to increased anxiety-related symptoms. Methods: The current investigation examined the utility of an IU-IB paradigm across two separate samples wherein participants completed an interpretation bias task and self-report measures. Sample 1 included 86 participants (74.4% female; M age = 19.14) and sample 2 included 138 participants (79.7% female; M age = 18.88). Results: Findings from Study 1 indicated a significant association between an exaggerated IU-IB and symptoms of GAD and OCD, and this relationship held after covarying for negative affect. Study 2 results indicated a significant relationship between an exaggerated IU-IB and symptoms of GAD, OCD, and SAD, after covarying for negative affect. Limitations: The current study had a variety of limitations, including the use of cross-sectional data and an undergraduate sample. Conclusions: These findings provide an important replication and extension of previous work and highlight the transdiagnostic utility of this IU-IB task. Highlights: Study 1 found an association between an exaggerated IU-IB and symptoms of GAD & OCD. This relationship held after covarying for negative affect. Study 2 found a relationship between IU-IB and symptoms of GAD, OCD, and SAD. These results remained after covarying for negative affect. Results support our IU-IB paradigm as a second method of assessment for IU.